ANALISIS PERATAAN LABA ( INCOME SMOOTHING ) : FAKTOR YANG MEMPENGARUHINYA DAN PENGARUHNYA TERHADAP RETURN DAN RISIKO SAHAM PERUSAHAAN GO PUBLIC DI BURSA EFEK JAKARTA - Irawati, Zulfa; Maya A, Anugerah (Benefit: Jurnal Manajemen dan Bisnis, 2007)
This research is designed to examine the income smoothing in Indonesia. Incomesmoothing can be defined as a means used by management to diminish the variability ofstream of reported income numbers relative to some perceived target stream by theÂ manipulation of artificial (accounting)Â and realÂ (transactional) variables (Koch, 1981).Three main issue investigated in this reseach were factor influencing income smoothing andthe income smoothing effect to return and risk (beta)Â of public companies stocks in Indonesia.Eighty three listed in Jakarta stock exchage (JSX)Â selected using purposive sampling methodwere used as reseach sample. The sample was then classified into smoother and nonsmoother using Eckelâs model, used income after tax. The result showed that 45 companiespracticed income smoothing and 38 companies didnât practiced income smoothing bycompanies listed in JSX.Common and special statical test according the hypothesis were used in this reseach.Common statical includes descriptive statistic, normality data test(with one sampelÂ kolmogorov smirnov)Â and population test with Mann Whitney test or t t est. All kind ofÂ common statical test concluded that data was distributed unnorrmally and the sample cameÂ from the same population.The first hypothesis examined whether NPS, Profitabilitas, Net Profit Margin,Leverage, Industrial sector, and winner losser stocks influenced income smoothing. Logisticregression was used to the test this hypothesis and concluded that the first hypothesis cannotrejected, so all the factors hypothesized were not influence income smoothing. The secondhypothesis examined whether there was return difference between smoother aand nonsmoother. This hypothesis was tested with independent sample t test and concluded that therewas no return difference between smoother and non smoother. The third hypothesis examinedwhether there was risk (Â beta)Â difference between smoother aand non smoother. ThisÂ hypothesis was tested with independent sample t test and concluded that there was no risk (beta) difference between smoother and non smoother.